INCREASING COMMUNITY PARTICIPATION CAPACITY IN PAUD PROGRAM THROUGH PARENTING EDUCATION AT PUSAT KEGIATAN BELAJAR MASYARAKAT - Ansori Ansori; Nunu Mahmud Firdaus (IKIP Siliwangi Bandung, 2020)
Early Childhood Education is an important program that must be carried out within the scope of the community who realized that the growth and development of children are important and needs attention. In this research, it has been determined PKBM Lentera Bangsa located in the PKBM Lentera Bangsa, Margahayu Selatan Village, Margahayu Sub-District, Bandung District to be the location of the research. Based on the identification results, it is found that the problem in the community is the difficulty of the PKBM institution in determining the appropriate parenting education model for parents of students in the Similar PAUD Units that provides a sustainable impact with community participation. Because there is a need for a solution to this problem, a parenting education program is implemented with the aim of increasing the capacity of community participation in the PKBM Lentera Bangsa. The target of this program is the parents of students in the Similar PAUD Units, PAUD teachers in Margahayu sub-district and Margaasih sub-district. The method of implementation is in the form of identifying program needs, preparing program plan recommendations, preparing plans and socializing program plans, implementing, evaluating and following up on programs. The results obtained are the discovery of a parenting education delivery model in the form of seminars for parents and teachers of Similar PAUD Units so that increasing community participation capacity is ongoing or can be carried out sustainably for the surrounding community.